ADAR RNA editing below the backbone - Keegan, Liam; Khan, Anzer; Vukic, Dragana; O'Connell, Mary (RNA (New York, N.Y.), 2017)
ADAR RNA editing enzymes (adenosine deaminases acting on RNA) that convert adenosine bases to inosines were first identified biochemically 30 years ago. Since then, studies on ADARs in genetic model organisms, and evolutionary comparisons between them, continue to reveal a surprising range of pleiotropic biological effects of ADARs. This review focuses on Drosophila melanogaster, which has a single Adar gene encoding a homolog of vertebrate ADAR2 that site-specifically edits hundreds of transcripts to change individual codons in ion channel subunits and membrane and cytoskeletal proteins. Drosophila ADAR is involved in the control of neuronal excitability and neurodegeneration and, intriguingly, in the control of neuronal plasticity and sleep. Drosophila ADAR also interacts strongly with RNA interference, a key antiviral defense mechanism in invertebrates. Recent crystal structures of human ADAR2 deaminase domain-RNA complexes help to interpret available information on Drosophila ADAR isoforms and on the evolution of ADARs from tRNA deaminase ADAT proteins. ADAR RNA editing is a paradigm for the now rapidly expanding range of RNA modifications in mRNAs and ncRNAs. Even with recent progress, much remains to be understood about these groundbreaking ADAR RNA modification systems.
Keywords: obratlovci; substrátová specifita; vztahy mezi strukturou a aktivitou; Protein Binding; ADAR; molekulární evoluce; Humans; RNA editing; dsRNA; Structure-Activity Relationship; adenosindeaminasa; Drosophila melanogaster; Drosophila Proteins; zvířata; proteiny vázající RNA; messenger RNA; RNA Interference; nervový systém; editace RNA; proteiny Drosophily; RNA interference; epitranscriptome; RNA modification; RNA-Binding Proteins; vazba proteinů; Protein Interaction Domains and Motifs; interakční proteinové domény a motivy; Gene Expression; Evolution, Molecular; Substrate Specificity; izoenzymy; Animals; Vertebrates; RNA, Messenger; lidé; Isoenzymes; Nervous System; RNA Editing; Adenosine Deaminase; exprese genu